USING THE INTERNET OF THINGS IN A PRODUCTION PLANNING CONTEXT - Alarcón, Faustino; Perez, David; Boza, Andrés (Brazilian Journal of Operations & Production Management, 2016)
One of the most novel concepts that has been applied to companies in recent years is “Sensing Enterprises”. This concept implies a drastic change in the way companies operate. Within the framework of this concept, another necessary and complementary concept arises, the so-called “Internet of Things” concept. It seems evident that the Internet of Things can generally help improve the function- ing of the processes undertaken in companies, particularly one of the key proc- esses; the production planning process. Despite being able to find abundant infor- mation on both themes, and the apparent relevance that using the Internet of Things could have for the production planning process, no works that have jointly studied these matters were found. To bridge this gap, the present work intends to reflect on how the characteristics and advantages of the Internet of Things can be put to good use in the production planning process.